The normal resolvability of the equations in convolutions in the Hölder’s functions spaces - Dolgonos, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Е. И. Долгонос. Нормальная разрешимость уравнений в свертках в пространствах гельдеровых функций E. Dolgonosas. Kompozicinių lygčių normalus išsprendžiamumas Hiolderio funkcijų erdvėse